Production of Whey Protein Edible Film: The Study of Protein and Glycerol Ratio on Physical and Chemical Properties (Jurnal Ilmu dan Teknologi Hasil Ternak, 2010)
The aim of the research was to know the effect of various protein: glycerol ratio as plasticizer onÂ  physical and chemical properties of whey protein edible film. The result of the research showed that there was highly significant effect (P<0.01) of the protein: glycerol ratio on the WVP, protein solubility, and moisture content. The G3 treatment with protein: glycerol ratio (1:1.5) gives lower values of the WVP, protein solubility, and moisture content. Microstructure of edible film appears unflat on treatment G1, flat on treatment G2 and porous on treatment G3 on its surface. Â  Keywords : edible film, whey protein, glycerol